On a new class of convex functions and integral inequalities - Shanhe Wu; Muhammad Uzair Awan; Muhammad Aslam Noor; Khalida Inayat Noor; Sabah Iftikhar (Journal of Inequalities and Applications, 2019)
Abstract The aim of this paper is to introduce a new extension of convexity called σ-convexity. We show that the class of σ-convex functions includes several other classes of convex functions. Some new integral inequalities of Hermite–Hadamard type are established to illustrate the applications of σ-convex functions.